Assessment of quality of life and psychologic aspects in patients with gestational trophoblastic disease - Ferreira, Erika Goulart Veloso [UNESP]; Maesta, Izildinha [UNESP]; Michelin, Odair Carlito [UNESP]; De Paula, Regina Celia Callile [UNESP]; Consonni, Marcos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (My University, 2009)
OBJECTIVE: To assess quality of life (QoL) and psycho-logical aspects in patients with gestational trophoblastic disease (GTD). METHODS: This cross-sectional self-report study was conducted among 54 women. Validated question-naires assessed QoL (WHO-QOL-bref), symptoms of de-pression (Beck Depression Inventory [BDI]) and anxi-ety (State-Trait Anxiety In-ventory [STAI]). RESULTS: Most patients rated overall QoL as good (44.44%) and were satisfied with their health status (42.59%). Mean QoL domain score was lowest for psy-chologic health (53.86 ±21.46) and highest for social re-lationships (65.74 ± 22.41). BDI mean was 15.81 ± 11.15, indicating dysphoria. STAI means were 46 ± 6.46 for trait-anxiety and 43.72 ±4.23 for state-anxiety, both evidencing medium-high anxiety. Among employed pa-tients, environment domain mean was the highest (p=0.024). Presence of children resulted in lowest means for physical health (p=0.041) and environment (p=0.045). Patients desiring children showed significantly higher means for physical health (p-0.004), psychologi-cal health (p=0.021) and environment (p=0.003). Chemotherapy had no signif-icant influence on QoL (p>0.05). CONCLUSION: This study evidenced psychological im-pact on GTD patients, sug-gesting specialized care centers should provide psychological interventions during treat-ment and follow-up of GTD patients, highlighting the importance of a multidisci-plinary approach. (J Reprod Med 2009;54:239-244).
Keywords: Gestational trophoblastic disease; Psychological aspects; Quality of life